2022
DOI: 10.1021/acsapm.2c00309
|View full text |Cite
|
Sign up to set email alerts
|

Auxetic Wearable Sensors Based on Flexible Triboelectric Polymers for Movement Monitoring

Abstract: The methods to enhance the output voltage of triboelectric nanogenerators based on polymeric dielectric materials, such as building micro−nano structure and chemical modification, probably lower the structural uniformity of their devices and then decrease the performance stability because of stress aggregation. Here, we proposed a strategy based on auxetic structures for improving the triboelectric performance, which could concurrently uniformize the stress transfer due to their excellent friction properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…This phenomenon can be explained from two aspects: one is excellent elasticity and good toughness of PA Film, the other one is the stronger shear resistance, fracture toughness and cracks propagation resistance of BSH-NPR structure. [28][29][30] It is particularly worth mentioning here that releasing the strain enables re-joining of electrode contacts (albeit incomplete) to recover conductivity when electrode is stretched until contact points completely separated and is non-conductive. This is enough to demonstrate that flexible electrodes prepared in this paper have certain self-recovery.…”
Section: Stretching Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon can be explained from two aspects: one is excellent elasticity and good toughness of PA Film, the other one is the stronger shear resistance, fracture toughness and cracks propagation resistance of BSH-NPR structure. [28][29][30] It is particularly worth mentioning here that releasing the strain enables re-joining of electrode contacts (albeit incomplete) to recover conductivity when electrode is stretched until contact points completely separated and is non-conductive. This is enough to demonstrate that flexible electrodes prepared in this paper have certain self-recovery.…”
Section: Stretching Testingmentioning
confidence: 99%
“…[1][2][3][4][5] However, conductivity of flexible electronic devices can't be guaranteed due to the lack of reliability of existing flexible electrodes under various deformation and many other fields due to unique auxetic properties and outstanding mechanical properties including stronger shear resistance, fracture toughness and cracks propagation resistance, etc. [27][28][29][30][31][32] It is worth mentioning that the NPR structure has been reported many times to have the ability to improve flexible electrode mechanical performance. [33][34][35][36][37] Weng et al compared between thin film electrode and NPR electrode, it is found that the stress level in the NPR electrode is relatively low due to the faster appearance of the inelastic deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39−41 Research has proved that the meta-concave structures of negative Poisson's ratio (NPR) can improve the mechanical properties and output performance of piezoelectric and 2D triboelectric devices. 42 Poly(vinylidene fluoride) (PVDF) is a ferroelectric polymer whose β-phase PVDF has high electron affinity, high spontaneous polarization, and excellent polarization stability and is an excellent TENGs triboelectric material. Therefore, we propose a two-step strategy to concave the cell and cell-packing structure of porous TENGs based on PVDF for improving their triboelectric output and mechanical performance concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, modification in the structural design of sensors, which can bring higher sensitivity, is free of component change, meaning it can avoid the reduction in mechanical properties induced by interfacial noncompatibility. Research has proved that the meta-concave structures of negative Poisson’s ratio (NPR) can improve the mechanical properties and output performance of piezoelectric and 2D triboelectric devices . Poly­(vinylidene fluoride) (PVDF) is a ferroelectric polymer whose β-phase PVDF has high electron affinity, high spontaneous polarization, and excellent polarization stability and is an excellent TENGs triboelectric material.…”
Section: Introductionmentioning
confidence: 99%